What Factors Impact upon a Woman’s Decision to Undertake Genetic Cancer Testing? - Quinlivan, Julie A.; Battikhi, Zain; Petersen, Rodney W. (Frontiers in Oncology, 2014)
Introduction: The advent of human genome project has lead to genetic tests that identify high-risk states for certain cancers. Many are privately marketed on the Internet. Despite the availability of tests, limited data has evaluated factors that lead to test uptake. The aim of the present study was to explore the attitudes of a cohort of new mothers towards uptake of a genetic cancer test with a 50% predictive value of cancer. Methods: A cross-sectional survey was undertaken. The project targeted women who had recently given birth at an Australian tertiary referral hospital. Women were asked about a theoretical blood test that detected an increased risk for the development of cancer. Attitudes and knowledge questionnaires were completed. Results: Of 232 consecutive women approached, 32 declined, giving a response rate of 86.2%. Only 63 (31.5%) women stated they would have the test. Absence of religious belief, higher level of education, better knowledge of terms used in genetics, an absence of concern over emotional, employment and insurance discrimination and previous acceptance of Down syndrome screening in pregnancy were each associated with significantly higher rate of test uptake in univariate analysis (all p< 0.03). In multivariate analysis, a lack of concern over discrimination and a history of having accepted Down syndrome screening in the previous pregnancy remained significantly associated with test uptake (all p< 0.0001). Conclusion: Concern over discrimination and having made a prior decision to have genetic testing were the principal factors associated with decision-making.